Knowledge and Organization: A Social-Practice Perspective - Brown, John Seely; Duguid, Paul (Organization Science, 2001)
While the recent focus on knowledge has undoubtedly benefited organizational studies, the literature still presents a sharply contrasting and even contradictory view of knowledge, which at times is described as “sticky” and at other times “leaky.” This paper is written on the premise that there is more than a problem with metaphors at issue here, and more than accounts of different types of knowledge (such as “tacit” and “explicit”) can readily explain. Rather, these contrary descriptions of knowledge reflect different, partial, and sometimes “balkanized” perspectives from which knowledge and organization are viewed. Taking the community of practice as a unifying unit of analysis for understanding knowledge in the firm, the paper suggests that often too much attention is paid to the idea of community, too little to the implications of practice. Practice, we suggest, creates epistemic differences among the communities within a firm, and the firm's advantage over the market lies in dynamically coordinating the knowledge produced by these communities despite such differences. In making this argument, we argue that analyses of systemic innovation should be extended to embrace all firms in a knowledge economy, not just the classically innovative. This extension will call for a transformation of conventional ideas coordination and of the trade-off between exploration and exploitation.